Analisis Kemampuan Literasi Sains Mahasiswa Calon Guru Kimia pada Materi Laju Reaksi - Ariska, Dwi Auliya; Junaidi, Eka; Hidayanti, Ermia (Chemistry Education Practice, 2024)
This research is descriptive research with a quantitative approach aimed at describing the scientific literacy abilities of prospective chemistry teacher students on reaction rate. This research involved 50 students as samples with a sampling technique using purposive sampling. The data collection technique uses a test instrument similar to PISA based on scientific literacy which is analyzed using descriptive statistics. From there validator the instrument of validity obtained was 0.803 for the content aspect and 0.747 for the language aspect and the reliability score obtained was 0.65 with high information. Based on the research results obtained, each aspect of scientific literacy received a low category. The results of this research indicate that the science literacy skill of the pre-service chemistry teacher students still need to be improved so that each indicator reaches sufficient numbers and overall scientific literacy abilities become better. Students' science literacy skill were obtained from four aspects of science literacy skill, including the knowledge aspect (34.86%), the context aspect (68.86%), the competency aspect (52.26%), and the attitude aspect (75.1%) so that it was obtained the average science literacy skill of the pre-service chemistry teacher students in the overall reaction rate is 57.78% in the low category.